Penguatan Jiwa Kewirausahaan Mahasiswa melalui Strategi Pemasaran Digital - Yudhi Novriansyah; Supriyati Supriyati; Herawati Herawati; Muhammad Asman; Ida Zuliyana (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2025)
Lectures of the Management Study Program at Muara Bungo University (UMB) have implemented a Community Service Program (PKM) to boost students' entrepreneurial spirit. This was carried out through a seminar and discussion with the theme "Strengthening the Entrepreneurial Spirit of Students through Digital Marketing Strategies" in the UMB Faculty of Economics Auditorium. It is hoped that the seminar and discussion, designed with a participatory learning approach, will enhance the entrepreneurial spirit of UMB Management Study Program students and teach them how to use digital marketing to start businesses and open ventures.